Evaluation of a real-time PCR and a loop-mediated isothermal amplification for detection of 'Xanthomonas arboricola' pv. 'pruni' in plant tissue samples - Palacio-Bielsa, Ana; Lopez-Soriano, Pablo; Buehlmann, Andreas; van Doom, Joop; Pham, Khanh; Cambra, Miguel A.; Berruete, Isabel M.; Pothier, Joel F.; Duffy, Brion; Olmos, Antonio; López, María M. (2017)
Operational capacity of real-time PCR and loop-mediated isothermal amplification (LAMP) diagnostic assays for detection of Xanthomonas arboricola pv. pruni was established in a ring-test involving four laboratories. Symptomatic and healthy almond leaf samples with two methods of sample preparation were analyzed. Kappa coefficient, sensitivity, specificity, likelihood ratios and post-test probability of detection were estimated to manage the risk associated with the use of the two methods.